Improving rice yield (Oryza sativa L.) and selected soil physicochemical properties using organic amendments under water-saving irrigation - Haque, Ahmad Numery Ashfaqul (2022)
Rice provides calories to more than half of the world's population, but consumes excessive water compared to other staple crops. To minimize this excess water usage alternate wetting and drying (AWD) irrigation practices are considered an efficient technique in which soil is intermittently irrigated. The addition of suitable organic amendments could help to retain soil moisture and improve physicochemical properties. In this context, four experiments were conducted to evaluate the effect of organic amendments on soil physicochemical properties for improved rice yield under water-saving irrigation. At first, an incubation study was conducted to evaluate the incorporation of five selected organic amendments—as follows: rice husk biochar (RHB), oil palm empty fruit bunch biochar (EFBB), compost, rice husk ash (RHA), and oil palm bunch ash (PBA), with a control (no amendment) on soil moisture storage and some chemical properties of soil. The soil was incubated with five amendments for 60 days and sampled at 15-day intervals. After completion of the incubation, RHB (0.46 g g-1) and EFBB (0.45 g g-1) exhibited greater gravimetric water content compared to the control (0.16 g g-1). PBA treatment produced maximum soil pH (6.95) compared to its initial value (5.01). EFBB finally contributed to the highest total carbon (7.82%) and nitrogen (0.44%). PBA showed the highest available phosphorus (P) and exchangeable potassium (K). The second study investigated the effect of water-saving irrigation with biochar and compost on the growth, yield, water productivity of rice and physicochemical properties of soil. A glasshouse experiment was executed with two irrigation regimes namely AWD and continuous flooding (CF) and four treatments including three types of organic amendments namely RHB, EFBB, and compost applied at 4% (weight/weight), and recommended fertilizer dose (RFD). Under the AWD irrigation regimes, maximum grain was produced by RHB (241.12 g) and the lowest in the RFD (210.15 g), whereas under the same organic amendments both AWD and CF produced similar grain yields. RHB and EFBB with AWD irrigation showed better water productivity (WP) (6.30 g L-1 and 5.80 g L-1, respectively) over control treatment under CF (3.94 g L-1). Within the same irrigation soil pH, cation exchange capacity, total carbon (C), and nitrogen (N) are enhanced by biochar and compost incorporation. RHB and EFBB significantly reduced soil bulk density up to 0.88 g cm-3 from 1.12 g cm-3 and enhanced porosity up to 58.7% compared to RFD in CF irrigation. The next study was conducted to investigate the effect of biochars on rice yield, fertilizer N use efficiency, and recovery under watersaving irrigation by a 15N isotopic tracer. Two types of irrigation AWD and CF, and four types of biochar treatments such as RHB with 15N urea, EFBB with 15N urea, 15N urea alone, and control, were applied. About 4% reduced grain yield (193.89 g pot-1) was achieved by the AWD regime over the CF (202.57 g pot-1, whereas RHB and EFBB with 15N urea significantly increased rice yield (up to 8.8%) compared to 15N urea alone. RHB and EFBB with 15N urea enhanced the fertilizer N recovery from 15N urea (0.59 g g-1 and 0.61 g g-1, respectively), over 15N urea alone (0.49 g g-1). Agronomic use efficiency and partial factor productivity of N were accelerated by RHB (32.77 g g−1 and 73.14 g g−1, respectively) and EFBB (33.77 g g−1 and 74.14 g g−1, respectively). The last experiment was conducted to assess the effect of biochar combined with fertilizer on physiological response, water productivity and nutrient use efficiency (NUE) of rice, and changes in biochemical properties of soil under AWD irrigation. Two types of irrigation practices such as AWD and CF and four types of fertilizer combinations namely T1: 25% RHB+75% of recommended fertilizer dose (RFD), T2: 25% EFBB+75% of RFD, T3: 100% RFD, and T0: 0% biochar and fertilizer were assigned. The AWD irrigation produced a sharply reduced grain yield (210.58 g pot−1) compared to CF irrigation (218.04 g pot−1), whereas the biochar combination treatments T1 and T2 produced greater yields (260.27 g pot−1 and 252.12 g pot−1, respectively), which were up to 12.5% higher than RFD (231.27 g pot−1). Within AWD, irrigation water usage by T1 and T2 (98.50 Land 102.38 L, respectively) was profoundly reduced by up to 28.8% over CF with T3 (138.25 L), with improved WP. The main effect of biochar treatment T1 and T2 also increased photosynthesis rate (21.31 and 20.950 μmol m−2s−1, respectively) compared to RFD (17.63 μmol m−2s−1), in addition to boosted agronomic efficiency of N, P and K compared to RFD. Nevertheless, T1 and T2 significantly enhanced the total carbon and nitrogen; dehydrogenase and urease enzyme activities also increased in both irrigation regimes. The results reveal that the integrated application of RHB and EFBB with the AWD regime highly reduces irrigation water and improves NUE, WP, and soil quality with a minimum yield penalty. Overall, the biochars not only boosted the soil C content and nutrient availability but also increased moisture content with better soil porosity. The addition of biochar in AWD irrigation is could be an efficient management system for improved rice yield with improved WP.